2007
DOI: 10.1080/00288230709510317
|View full text |Cite
|
Sign up to set email alerts
|

Response of vegetation and soils to desertification of alpine meadow in the upper basin of the Yellow River, China

Abstract: Alpine meadow plays important roles in the animal production and conservation of water resources in the upper basin of Yellow River. In recent decades, desertification of this alpine meadow has resulted in changes in vegetation and soil features, as well as threatening the ecosystem functions and security. A field study was conducted to explain the response of vegetation pattern and soil features to desertification of alpine meadows. Results of vegetation studies indicated that hygrophytes were gradually repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A small number of species on less moistened and highly compact locations due to higher soil bulk density than other locations suggested that soil compactness contributed to species loss (Wang et al 2007). Intensity of scraping, grazing and trampling may alter the habitat suitability for many species (Pandey and Shukla 1999;Sagar et al 2003).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A small number of species on less moistened and highly compact locations due to higher soil bulk density than other locations suggested that soil compactness contributed to species loss (Wang et al 2007). Intensity of scraping, grazing and trampling may alter the habitat suitability for many species (Pandey and Shukla 1999;Sagar et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Overgrazing together with less soil moisture may convert fertile grassland into a desert (Singh et al 2006). However, increased soil bulk density could be a surrogate measure for increased desertification (Wang et al 2007). Thus, it can be inferred that desertification leads to loss in species diversity by reducing the soil moisture content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alpine meadows account for 89.5% of the total land area of the study area (Wang et al . ). The study area was previously grazed by yak and Tibetan sheep but was fenced in to exclude grazing by livestock and human disturbances in 2005 because it was made part of a natural protection zone.…”
Section: Methodsmentioning
confidence: 97%
“…For the SW landform, SOM was found to be influenced by NDVI as well (R 2 =0.84; Table 1). This is because a large amount of dead plants might be accumulated in the areas with this landform (Jia et al, 2006;Wang et al, 2007) and higher soil moisture can prompt chemical processes to convert those dead plants into organic matter (Quideau et al, 2001;Yang et al, 2008). In summary, SOM and NDVI were found to be positively associated for each of the nine landforms, but the associations were distinctly different from one landform to another (Fig.…”
Section: Associations Between Som and Landformmentioning
confidence: 99%